Strategies for developing the religious and moral aspects of early childhood - Permana, Ayu Intan; Nurhafizah, Nurhafizah; Wahyu Adibah, Khairiyyah Titi (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
Religious and moral development is essential to early childhood education; therefore, it is necessary to implement development strategies. This study aimed to explain the strategy for fostering young children's religious and moral development. This is qualitative research employing a literature review methodology. Collecting articles, reducing articles, presenting articles, explaining articles, and drawing conclusions comprised the data analysis technique. The findings revealed that media for fostering religious and moral development include Alqur'an learning media, digital animation media, Educational Game Tools, BEAT application media, ICT (Information and Communication Technology), VCDs, and student worksheets. While the strategies for developing religious and moral aspects in young children are exemplary, they include playing while learning, the Montessori method, the PAIKEM model, behavior development, habituation, storytelling, demonstration methods, and programs for character education. In conclusion, the strategy for fostering religious and moral development in young children can be implemented through various media and instructional techniques.